(Global) health geography and the post‐2015 development agenda. Issue 2 (12th December 2013) - Herrick, Clare
<x xml:space="preserve">Abstract</x> This commentary complements and extends Brown and Moon's (2012) work on 'geography and global health' by starting where their piece finished – the post‐2015 development agenda. It explores three core elements of this agenda: the debate over the revised Millennium Development Goals, new Sustainable Development Goals and the inclusion of non‐communicable disease within both. It then critically reflects on the significance of this for three areas of geographical engagements with global health in particular, and health in more general terms: the (re)integration of health and the urban; shifts in global funding priorities; and the genesis and effects of what have been termed 'industrial epidemics'.